The impact of adding weight-bearing exercise versus nonweight bearing programs to the medical treatment of elderly patients with osteoporosis - Alsayed A Shanb; Enas F Youssef (Wolters Kluwer Medknow Publications, 2014)
Background: Osteoporosis is a major public health problem affecting the elderly population, particularly women. The objective of the study was to evaluate the effects of adding weight-bearing exercise as opposed to nonweight-bearing programs to the medical treatment of bone mineral density (BMD) and health-related quality of life (HRQoL) of elderly patients with osteoporosis. Materials and Methods: Participating in the study were 40 elderly osteoporotic patients (27 females and 13 males), with ages ranging from 60 to 67 years, who were receiving medical treatment for osteoporosis. They were assigned randomly into two groups: Group-I: Twenty patients practiced weight-bearing exercises. Group-II: Twenty patients did nonweight-bearing exercises. All patients trained for 45-60 min/session, two sessions/week for 6 months. BMD of the lumbar spine, right neck of femur, and right distal radial head of all patients were measured by dual-energy X-ray absorptiometry before and after both treatment programs. In addition, the QoL was measured by means of the HRQoL "ECOS-16" questionnaire. Results: T-tests proved that mean values of BMD of the lumbar spine, right neck of femur and right distal radial head were significantly increased in both groups with greater improvement in the weight-bearing group. The QoL was significantly improved in both groups, but the difference between them was not significant. Conclusion: Addition of weight-bearing exercise program to medical treatment increases BMD more than nonweight-bearing exercise in elderly subjects with osteoporosis. Furthermore, both weight-bearing and nonweight-bearing exercise programs significantly improved the QoL of patients with osteoporosis.